Criminalization of Pornography: Assessing the Limits of “Intent” in Indonesian Criminal Law - Muwafiq Zaid; La Ode Husein; Sutiawati Sutiawati (Faculty of Law, Universitas Muslim Indonesia, 2025)
The criminalization of pornography in Indonesian criminal law raises significant interpretative challenges, particularly in determining the boundaries of intent (dolus) and criminal liability in the digital era. This study aims to analyze the legal qualification of the act of intentionally creating pornographic content and to examine the extent of criminal responsibility when such content is disseminated without the direct intent or control of the creator. Employing a normative juridical method with a case approach, this research focuses on Decision Number 51/Pid.B/2021/PN.Mgn as an empirical basis for analysis. The findings reveal that the application of law in such cases tends to emphasize the fulfillment of actus reus while insufficiently examining the element of mens rea, particularly the intent to distribute or make the content accessible to the public. The case demonstrates that the defendant’s intent was limited to private recording, whereas the dissemination occurred due to third-party intervention. This condition raises critical issues regarding causality, where the concept of novus actus interveniens should be considered as a factor that breaks the chain of criminal liability. The study also identifies a tendency toward overcriminalization, resulting from a formalistic interpretation of legal provisions without adequate consideration of context, proportionality, and individual fault. This research contributes to the existing literature by offering a novel perspective on the reinterpretation of intent in pornography-related offenses, particularly in situations involving loss of digital control. It argues for a more contextual and substantive approach in assessing criminal liability, distinguishing clearly between private acts and public consequences. The study recommends legislative reform to clarify the boundaries between the creation and dissemination of pornographic content, as well as the development of judicial guidelines to ensure consistent and proportionate law enforcement in the digital age.